The condition of the right to adequate housing for LGBT+ people in Chile - Méndez, Nicolás; Rodríguez-Matta, Paula (Revista de Urbanismo, 2023)
Two decades ago, government production of statistical data on LGBT+ people were uncommon. This implied problems in the design of urban social policies. Social organizations made up for this lack, generating information about LGBT+ human rights, without delving into the right to adequate housing. This article seeks to contribute to the production, management, and analysis of information on the right to adequate housing. To do this, a review is carried out of each of the seven key elements of this right: security of tenure, availability of services, bearable expenses (affordability), habitability, accessibility, location (place) and cultural appropriateness. Although there is a set of legal initiatives that protect LGBT+ rights, the result of the analysis is that, in each of the key elements of the law, various conflicts occur that LGBT+ people face for the production and management of urban space, homes, neighbourhoods and cities, around spatial justice.